Relation between hearing abilities and preferred playback settings for speech perception in complex listening conditions. (1st November 2022) - Kubiak, Aleksandra M.; Rennies, Jan; Ewert, Stephan D.; Kollmeier, Birger
Abstract: Objective: This study investigated if individual preferences with respect to the trade-off between a good signal-to-noise ratio and a distortion-free speech target were stable across different masking conditions and if simple adjustment methods could be used to identify subjects as either "noise haters" or "distortions haters". Design: In each masking condition, subjects could adjust the target speech level according to their preferences by employing (i) linear gain or gain at the cost of (ii) clipping distortions or (iii) compression distortions. The comparison of these processing conditions allowed investigating the preferred trade-off between distortions and noise disturbance. Study sample: Thirty subjects differing widely in hearing status (normal-hearing to moderately impaired) and age (23–85 years). Results: High test–retest stability of individual preferences was found for all modification schemes. The preference adjustments suggested that subjects could be consistently categorised along a scale from "noise haters" to "distortion haters", and this preference trait remained stable through all maskers, spatial conditions, and types of distortions. Conclusions: Employing quick self-adjustment to collect listening preferences in complex listening conditions revealed a stable preference trait along the "noise vs. distortions" tolerance dimension. This could potentially help in fitting modern hearing aid algorithms to the individual user.